The genesis of staff-student partnerships: Institutional influences - Smith, Susan; Axson, Dan (International Journal for Students as Partners, 2023)
As staff-student partnership activity becomes embedded into the infrastructure of higher education there is an increased institutional focus on systematising the staff-student partnership support processes. Drawing on data from a case study of a partnership conceived under the auspices of an institutional staff-student partnership programme, this article offers insight into how the institutional context shapes partnership aims, objectives, and composition. It finds that in the pre-partnership phase a gatekeeping role is performed by the institutional programme, which ultimately determines which partnerships proceed, and how they are evaluated. The study contributes to the broader critique of staff-student partnership practices, proposing a framework that integrates the various institutional influences and the pre and post-partnership phases.